Optimalisasi Proses Bisnis PT Veteri dengan Pendekatan Business Process Management - nasution, Anita hakim; Zafriana, Lusi (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
In the digital era, Micro, Small, and Medium Enterprises (MSMEs) face challenges in managing various distribution channels and adapting to constantly changing customer demands. PT Veteri, an MSME based in Surabaya that produces chewable gummy supplements for pets, encounters several business process issues, such as suboptimal workflows, slow customer response times, manual record-keeping, and excessive costs in non-core processes. This study aims to analyze and evaluate the business processes in the production and marketing divisions of PT Veteri using a Business Process Management (BPM) approach. The methods used include collecting quantitative and qualitative data, process analysis, designing a new business model, and measuring the impact after implementation. The findings show that by applying BPM, the company can redesign its processes to be more effective and efficient, particularly in terms of timeliness and cost efficiency. The recommendations include digitizing records, optimizing production flows, and improving customer-oriented digital marketing strategies